DESIGNING WAREHOUSE INVENTORY MANAGEMENT APPLICATION WEB-BASED ON BATIK SINUWUN SME WITH THE AGILE SCRUM DEVELOPMENT METHOD - Muhammad Yumna Majdina; Budi Praptono; Maria Dellarosawati Idawicaksa (Center for Study and Journal Management FTI UMI, 2020)
In this era, technology develops rapidly. More adequate and modern technology displaced old technology and indicates high competition. This competition requires changes in the management of a particular business in order to keep up with developments and take advantages of the application of technology. Sinuwun Batik is SME engaged in the production of batik clothes and selling batik clothes. The increasing number of requests and various types of SME make Batik Sinuwun overwhelmed in regulating the supply of raw materials for production, because there is no warehouse record. This study aims to design a website-based application that can help Batik Sinuwun SME to manage warehouse inventory.This inventory application is designed using the Agile Scrum Development method. The stages of making the system begin with collecting the required data by eliciting user needs, this data is the basic data in determining the features of application. This application is made based on websites using the PHP framework CodeIgniter and MySQL as data storage. The application system is tested using the Blackbox Testing method and ISO: 9126.The result of this research is a website application to simplify the management of raw materials in and out of the warehouse so that the latest stock of raw materials can be found, but it can also minimize recording errors due to manual calculations.